Meningkatkan Prestasi Siswa Materi Ekosistem Melalui Model Pembelajaran Kooperatif TAI (Team Assisted Individualization) - Asmawati (Action Research Journal, 2024)
The abstract is a brief and comprehensive summary of the contents of the article; it allows readers to quickly survey the contents of an article and, like the title, it allows people interested in the document to retrieve it from abstracting and indexing databases. The abstract contains at least the objectives, methods, results and conclusions of the research you have developed. A good abstract is one that is accurate, non-evaluative, coherent, easy to read, and concise. Do not exceed the abstract word limit of the journal where you submit your article. Word limits vary from journal to journal and usually range from 150 to 250 wordsThis research aims to improve student learning achievement in ecosystem material by implementing the TAI (team-assisted individualization) cooperative learning model. This type of research is classroom action research, which is carried out in two cycles. Each cycle consists of planning stages, action implementation, observation, and reflection. The subjects in this research were 32 class X students. Data collection is carried out through observation and tests. The research instruments used were observation sheets and test instruments. The data was analyzed qualitatively and quantitatively. 1) Improved Student Performance: There is a significant increase in student academic performance from pre-cycle to cycle 2. This indicates that the learning strategies implemented have been effective in increasing student understanding and achievement. 2) Effectiveness of Learning Strategy Changes: An increase in the average score and percentage of classical completion shows the success of the learning strategy changes that have been made during the learning cycle process. This confirms that adjustments to learning methods have had a positive impact on student learning outcomes. 3) Decrease in the number of incomplete students: The decrease in the number of incomplete students from cycle 1 to cycle 2 indicates an increase in the quality of learning. This shows that the additional efforts made to overcome learning challenges have succeeded in reducing the number of students who have difficulty achieving learning targets.